Application of mPEG-CS-cRGD/Bmi-1RNAi-PTX nanoparticles in suppression of laryngeal cancer by targeting cancer stem cells - Xiaoyan Xu; Tianhao Zhou; Xudong Wei; Xuelian Jiang; Jiyan Cao (Taylor & Francis Group, 2023)
AbstractAlthough surgery-based comprehensive therapy is becoming the main approach to treat laryngeal cancer, recurrence, metastasis, radiotherapy resistance and chemotherapy tolerance are still the main causes of death in patients. Targeted inhibition of laryngeal cancer stem cells has been considered as the consensus to cure laryngeal cancer. Our previous study has confirmed proto-oncogene Bmi-1 as a key regulator for self-renewal of laryngeal cancer stem cells. Targeted knockdown of Bmi-1 gene effectively inhibited the self-renewal and differentiation of laryngeal cancer stem cells, leading to the promoted sensitivity to chemotherapy including paclitaxel. However, due to off-target effects and quick degradation of the naked Bmi-1-RNAi small RNA oligo by nuclease in body fluids, it is urgently needed to develop a tumor-targeted delivery system with a protective shell. In this study, we designed and synthesized cRGD peptide-modified chitosan-polyethylene glycol slow-release nanoparticles (mPEG-CS-cRGD/Bmi-1RNAi-PTX) containing Bmi-1RNAi siRNA oligo and paclitaxel, which showed spherical in shape, 200 nm diameter in size, low cytotoxicity, strong DNA wrapping, resistance to nuclease degradation and high transfection efficiency to cells. Functional analysis indicated significant suppression of cell proliferation and migration and induction of apoptosis by the nanocomplex in laryngeal cancer cells in vitro. By application to the mouse model with laryngeal cancer, the nanocomplex inhibited tumor growth significantly in vivo. In addition, cRGD peptide, paclitaxel and Bmi-1 siRNA in the nanoparticles showed synergistic effects to suppress laryngeal cancer stem cells. In conclusion, this study not only developed a laryngeal tumor-targeted chemotherapeutic system, but also demonstrated a Bmi-1 RNAi-based chemotherapeutic strategy to inhibit cancer stem cells, having strong potential to treat laryngeal cancer patients suffering therapy resistance and/or tumor recurrence.